HUBUNGAN KECERDASAN EMOSIONAL DENGAN MINAT BELAJAR SISWA KELAS IV SDN 173418 POLLUNG - Novia Banjarnahor; Regina Sipayung; Darinda Sofia Tanjung (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This study aims to determine the relationship between emotional intelligence and learning interest in fourth grade students of SDN 173418 Pollung. The sample in the study consisted of 34 students. This type of research is quantitative. The data collection tool used to determine student learning motivation was a questionnaire that had been tested for validation and reliability. Both classes are normally distributed because Lhitung ≤ Ltabel. From the Linearity test, it is known that the significant value of deviation from linearity is 1.80 ≤ 3.32, it can be concluded that there is a linear relationship between emotional intelligence and student learning interest. The t test was conducted at the real level (α = 0.05) that tcount ≥ t_ (table), namely 5.925 ≥ 2.306, this proves that Ha is accepted, so the author concludes that there is a significant relationship between emotional intelligence and the learning interest of fourth grade students of SDN 173418 Pollung.Keywords: Relationship, Emotional Intelligence, Learning Interest.